Changes in knowledge of cervical cancer following introduction of human papillomavirus vaccine among women at high risk for cervical cancer - L. Stewart Massad; Charlesnika T. Evans; Kathleen M. Weber; Gypsyamber D'Souza; Nancy A. Hessol; Rodney L. Wright; Christine Colie; Howard D. Strickler; Tracey E. Wilson (Elsevier, 2015)
Purpose: To describe changes in knowledge of cervical cancer prevention, human papillomavirus (HPV), and HPV vaccination among women at high risk for cervical cancer in the first five years after introduction of HPV vaccination. Methods: In 2007, 2008-9, and 2011, women in a multicenter U.S. cohort study completed 44-item self-report questionnaires assessing knowledge of cervical cancer prevention, HPV, and HPV vaccination. Results across time were assessed for individuals, and three study enrollment cohorts were compared. Knowledge scores were correlated with demographic variables, measures of education and attention, and medical factors. Associations were assessed in multivariable models. Results: In all, 974 women completed three serial questionnaires; most were minority, low income, and current or former smokers. The group included 652 (67%) HIV infected and 322 (33%) uninfected. Summary knowledge scores (possible range 0-24) increased from 2007 (12.8, S.D. 5.8) to 2008-9 (13.9, S.D. 5.3, P < 0.001) and to 2011 (14.3, S.D. 5.2, P < 0.0001 vs 2007 and <0.04 vs 2008-9). Higher knowledge scores at first and follow-up administration of questionnaires, higher income, and higher education level were associated with improved knowledge score at third administration. Women not previously surveyed had scores similar to those of the longitudinal group at baseline. Conclusion: Substantial gaps in understanding of HPV and cervical cancer prevention exist despite years of health education. While more effective educational interventions may help, optimal cancer prevention may require opt-out vaccination programs that do not require nuanced understanding.